Review: Potency and Problem in Development of Self-reliance of Traditional Drug Raw Material in Indonesia - Suliasih, Babay Asih; Mun'im, Abdul (Pusat Inovasi Sains, 2022)
The use of herbs for health purposes has been practiced for thousands of years, long before the discovery of synthetic chemical drugs. Indonesia is widely recognized for its vast biodiversity, boasting approximately 30,000 plant species, equivalent to 75% of the total plant species worldwide, earning it the title of a mega-centre of global biodiversity. This highlights Indonesia's enormous potential in the traditional medicine industry, with the capability to compete on a global scale. However, several challenges hinder the development of traditional raw materials and the production of traditional medicines. These include herbal raw materials that fail to meet quality standards, a non-conducive business climate, limited technological advancements in the extraction and production of raw materials, uneven distribution of third-party laboratories across Indonesia which making it difficult for small and medium-sized industries to access product testing facilities, the exclusion of traditional medicines from the National Health Insurance (JKN) program, and a lack of empirical evidence for many plants with potential as traditional medicines. To address these challenges, intensive support and synergy from the government and legislative bodies are essential to enact policies that accelerate the growth of the traditional medicine industry. Additionally, strong collaboration with business actors, academics, and community organizations is crucial to fostering self-sufficiency in traditional medicine raw materials.